FACTORS RELATED TO WORK FATIGUE ON TRUCK DRIVERS AT PT KORDON PUTRA IN SUMEDANG REGENCY IN 2022 - Sulaeman, Dadang; Fauzi, Rizki (PHSAJ - Public Health Sebelas April Journal, 2022)
Fatigue is caused by several factors, namely workload, work capacity, and additional burden due to the work environment. Individual factors on fatigue such as age, workload, and nutritional status have a strong influence on causing fatigue. The purpose of this study was to determine the relationship between age, workload, nutritional status with work fatigue on truck drivers at PT Kordon Putra, Sumedang Regency. This research method used quantitative research with a cross sectional approach. The population in this study were 140 truck driver employees and the research sample was 58 truck driver. The instrument used was distributing questionnaires to respondents. Data were analyzed using chi square. The results of this study found that there was a relationship between age (p = 0.000) with work fatigue, workload (p = 0.000) with work fatigue, nutritional status (p = 0.000) with work fatigue. It is hoped that PT Kordon Putra will provide more education to truck driver employees and to minimize the safety of truck driver employees when driving trucks.